Experience as a Source for the Creation of Ethnic Music Compositions 'Lho' - Muhammad Fabian Arrizqi (International Journal of Seocology, 2022)
Personal experience as the idea of ​​creating music has its own challenges, because the creative process requires carefulness in sorting out what experiences will be transformed into music. This study adopted the Alma M. Hawkins dance creation method which explains that there are 3 stages in the creation of dance, namely exploration, improvisation and formation. The author adds several stages so that there are 5 stages, namely initial stimulation, inspiration, exploration, improvisation and formation. This composition uses a collaboration of western instruments, clarinet, guitar, bass, piano, xylophone, and eastern Sundanese lute and bebano.